The Dynamics of Consumer Psychology of Street Food Transformation and Preferences in Indonesia: Systematic Literature Review - Efandi, Satria; Indrayeni, Wiwik (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
Street food has become an increasingly popular phenomenon in Indonesia, creating changes in the culinary landscape and resulting in various changes in consumer preferences. This research aims to produce literature review material regarding the dynamics of consumer psychology regarding transformation trends and street food preferences in Indonesia. This research focuses on a deeper understanding of how psychological factors influence the way consumers perceive, choose and evaluate transformed street food. In this context, the research will explore the role of emotions in food decision making, identify the impact of perceived food quality on consumer preferences, and investigate the role of nostalgia in connecting consumers with street food. Apart from that, the research will also consider social and cultural factors that influence consumer preferences for street food in Indonesia. Through a careful literature review, this research will detail key findings related to this topic and identify trends, gaps in knowledge, and future research directions that can provide deeper insight into the complexities of consumer psychology in the context of street food in Indonesia. It is hoped that the results of this literature review will provide a better understanding of changes in street food trends and preferences.